O papel do servidor técnico administrativo na gestão universitária do campus da Universidade Federal do Ceará no Cariri - Silva, Luiza Virgínia de Castro (2010)
The main aim of this work is to investigate the competences of the technical-administrative servant in the restructuration of the public higher education. That identification was found in the literature and in the studied reality. In the development of the study a bibliographical an documentary survey was canned out about the university expansion since its beginning, focusing on this expansion which took place in Brazil, in order to the necessary understanding to establish the present, carried out itself bibliographical hoist and documentary about the expansion of the University since his sprouting, with approach for the university expansion occurred in Brazil, in order to seek the necessary understanding for establish the present governmental orientations on public policies for expanding the public higher education. The program to support restructuring and expansion of Federal Universities (REUNI) was identified legally established constitutes a governmental project to expand and restructure the Brazilian public higher. It highlights direction taken by the Federal University of Ceará in its adhesion term to the program aiming to identify the main objective of this work. In this expansionist reality the technical administrative officials were chosen for analysis due to their peculiarities and urgent needs to be inserted in a competent way, in the University management as committed collaborators with the organizational efficacy of the University. It was also employed a theoretical substantiation based upon a strategic planning for management of personal, so as to offer a basis for verifying strategic actions proposed by technical administrative officials of the UFC Campus in Cariri, this composing the Organization Strategic addressing for the public politics come back for the expansion of the public higher education. It identified itself the Program of Support to Restructuration and Expansion of the Federal Universities (REUNI), established in law, present governmental project for expansion and restructuration of the Brazilian public higher education, highlighting the addressings taken by the Federal University of Ceara in his Term of Adhesion to the program with an aim to identify the main objective of this work. In this Expansionist reality, the technical-administrative servants were chosen for analysis, given his peculiarities and the need of the immediate implementation, of competent way in the university management as the collaborators committed with the organizational efficacy of the University. It was employed also a theoretical substantiation based in the strategic planning of the management of persons, in order to offer foundation for the verification of the strategic actions strategic proposals by the technical-administrative servants of the Campus of the Federal University of Ceara in the Cariri between 2009 and 2012. The search for data occurred by means of primary and secondary sources presidential documents and pieces of the institution, as well as occasional observations and consultation to some manages. The proposal has identified competences addressed to the technical administrative officials intending their valorization, the increase of their role in the development of their management activities played in this Campus involving them processes of decision making through the awareness of their role as part of the organization of the reach of excellence related to the services done and avoiding the waste of available resources with the commitment to quality and outstanding organization.